2003
DOI: 10.1034/j.1398-9995.2003.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and immunological characterization of Pen ch 18, the vacuolar serine protease major allergen of Penicillium chrysogenum

Abstract: Our results confirm that the Pen ch 18 allergen is a vacuolar serine protease of P. chrysogenum that matures through N- and possibly C-terminal processing. The finding that there are cross-reactive and allergen-specific IgE epitopes for Pen ch 18 and Pen ch 13 suggests that both major allergens should be included in clinically diagnostic P. chrysogenum extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…Besides N-terminal cleavage, the mature vacuolar serine proteases may also undergo C-terminal processing [15, 20]. Similar to that reported for the vacuolar serine protease from C. albicans [17], the deduced cDNA sequence of Rho m 2 does not have a C-terminal extension.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Besides N-terminal cleavage, the mature vacuolar serine proteases may also undergo C-terminal processing [15, 20]. Similar to that reported for the vacuolar serine protease from C. albicans [17], the deduced cDNA sequence of Rho m 2 does not have a C-terminal extension.…”
Section: Discussionmentioning
confidence: 56%
“…IgE cross-reactivity between the group 18 (Pen ch 18) and the group 13 (Pen ch 13) major allergens from P. chrysogenum has been reported [20]. In addition, we have also demonstrated IgE cross-reactivity among serine protease allergens from P. oxalicum, P. chrysogenum and P. citrinum [22], as well as from A. fumigatus , P. chrysogenum and P. oxalicum [23].…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, IgE binding of rPer a 10 was completely inhibited when pooled patients' sera were preabsorbed with 500 g of self-protein in immunoblot inhibition, and there was no inhibition in C. lunata serine protease, which showed clear bands. Serine proteases are reported from many sources, and most of them are cross-reactive allergens (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that FUM20 can bind a synthetic peptide with sequence encompassing the N-terminal 23 residues of the mature Pen ch 18 [11]. mAb FUM20 also recognizes a class of pan-fungal allergens.…”
Section: Introductionmentioning
confidence: 99%